2011
DOI: 10.1182/blood-2011-07-368746
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and molecular profiles of erythroid cells after hydroxyurea treatment in sickle cell anemia

Abstract: Hydroxyurea has been shown to be efficacious for the treatment of sickle cell anemia (SCA), primarily through the induction of fetal hemoglobin (HbF). However, the exact mechanisms by which hydroxyurea can induce HbF remain incompletely defined, although direct transcriptional effects and altered cell cycle kinetics have been proposed. In this study, we investigated potential epigenetic and alternative molecular mechanisms of hydroxyurea-mediated HbF induction by examining methylation patterns within the G ␥-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 43 publications
4
72
0
Order By: Relevance
“…It has also been shown that BCL11A occupies the LCR HS3 and the intergenic region between G γA and δ-globin genes [31]. Acetylation-based transcriptional activity has been observed in the LCR, δ- and β-globin genes as well as the intergenic region between A γ and δ-globin genes, whereas methylation was most observed in the CpG islands of the γ-globin proximal promoter [38,84]. Furthermore, HU-induced HbF has previously been inversely correlated to Gγ-globin methylation in SCD patients [84].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that BCL11A occupies the LCR HS3 and the intergenic region between G γA and δ-globin genes [31]. Acetylation-based transcriptional activity has been observed in the LCR, δ- and β-globin genes as well as the intergenic region between A γ and δ-globin genes, whereas methylation was most observed in the CpG islands of the γ-globin proximal promoter [38,84]. Furthermore, HU-induced HbF has previously been inversely correlated to Gγ-globin methylation in SCD patients [84].…”
Section: Resultsmentioning
confidence: 99%
“…Acetylation-based transcriptional activity has been observed in the LCR, δ- and β-globin genes as well as the intergenic region between A γ and δ-globin genes, whereas methylation was most observed in the CpG islands of the γ-globin proximal promoter [38,84]. Furthermore, HU-induced HbF has previously been inversely correlated to Gγ-globin methylation in SCD patients [84]. Albeit, the changes in methylation did not reach statistical significance, decreases in methylated CpG islands in the Gγ-globin promoter were identified and associated with increased γ-globin expression.…”
Section: Resultsmentioning
confidence: 99%
“…40 The role of miRNAs in drug-mediated g-globin activation has also been investigated. Walker et al 41 verified that miR-26b was correlated with steady-state HbF levels in children with sickle cell disease, and miR-151-3p expression was associated with the maximal tolerated dose of hydroxyurea.…”
Section: Discussionmentioning
confidence: 99%
“…48 There is however, even in the case of HU-induced expression of Hb, some evidence for an epigenetic regulation, perhaps mediated by micro-RNA's (miRNAs). 49 The role of inactivation of repressor genes has also been recently documented as before said.…”
Section: ) Quantitative Trait Locimentioning
confidence: 93%